2012
DOI: 10.1111/j.1365-2427.2012.02803.x
|View full text |Cite
|
Sign up to set email alerts
|

Mussel responses to flood pulse frequency: the importance of local habitat

Abstract: Summary 1. Understanding mechanisms behind the distribution of organisms along a gradient of hydrological connectivity is crucial for sustainable management of river–floodplain systems. We tested the hypothesis that frequency of flood pulses exerts a direct influence on the distribution of freshwater mussels (Unionoida) by creating a local environment that limits their fitness. 2. Multiscale habitat analyses combined with transplant‐rearing experiments were carried out with a focus on abundance, presence/absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 44 publications
2
39
0
Order By: Relevance
“…Therefore, an improved understanding of macrozoobenthic assemblages is highly significant for developing efficient conservation and management strategies for floodplains. As is well-known, the distribution of benthic invertebrates in floodplain systems is influenced by abiotic habitat parameters such as water depth, current velocity, substratum stability, and grain size (Thomaz et al, 2007;Davidson et al, 2012;Negishi et al, 2012). Johnson et al (2004) showed that the variation of macrozoobenthic communities across sites in lakes is best explained by habitat-scale characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an improved understanding of macrozoobenthic assemblages is highly significant for developing efficient conservation and management strategies for floodplains. As is well-known, the distribution of benthic invertebrates in floodplain systems is influenced by abiotic habitat parameters such as water depth, current velocity, substratum stability, and grain size (Thomaz et al, 2007;Davidson et al, 2012;Negishi et al, 2012). Johnson et al (2004) showed that the variation of macrozoobenthic communities across sites in lakes is best explained by habitat-scale characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted between 16 June 2008 and 19 August 2010 within a 15-km mid-segment of the Kiso River (see Negishi et al, 2012a for more details). The channel gradient was 0.15% with an average wetted main-channel width of c. 400 m during the base-flow period.…”
Section: Study Sitementioning
confidence: 99%
“…FPWs had a negligible abundance of macrophytes possibly due to hydraulic conditions unsuitable for their growth. frequency ranging from 0-to 0.85-year return periods; 0-year return period was applied to connected FPWs (see Negishi et al, 2012a for more details). Additionally, the main channel was also sampled at a near-shore (<20 m from the shore) sampling station (Table 1).…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations